Dynamics in Circulating Proinflammatory Biomarkers for Prognostic Assessment of Patients With Advanced HCC – A Substudy From the SORAMIC Trial - Schütte, Kerstin; Kupčinskas, Juozas; Morkunas, Egidijus; Öcal, Osman; Schinner, Regina; Seidensticker, Max; De Toni, Enrico N.; Ben Khaled, Najib; Pech, Maciej; Palmer, Daniel; Berg, Thomas; Sengel, Christian; et al. (Frontiers in Gastroenterology, 2022)
Introduction Prediction of response to treatment in patients with advanced hepatocellular carcinoma (HCC) may assist in the selection of personalized management. Objective This exploratory analysis of the palliative arm of the SORAMIC trial (ClinicalTrials.gov NCT01126645) evaluated the prognostic potential of basal and dynamic changes in systemic levels of interleukin 6 (IL-6), interleukin 8 (IL-8), systemic vascular endothelial growth factor (VEGF), and lipopolysaccharide (LPS). Methods We evaluated the correlations between overall survival (OS) and concentrations of IL-6, IL-8, VEGF, and LPS at follow-up approximately 7-9 weeks after treatment initialization (FU) compared to baseline (BL) in 90 patients treated either with 90Yttrium (90Y) microspheres combined with sorafenib (n = 44) or with sorafenib (n = 46) alone. Results Changes in IL-6 concentration during treatment showed correlations with the outcome. An increase in IL-6 concentration of less than 16.8 pg/mL over baseline readings was associated with better survival [median OS 16.3 months compared with 8.9 months (p = 0.0354)]. Correlations with survival were not observed for VEGF or LPS concentrations at baseline, at FU, or changes between these time points. Conclusions Changes in IL 6 serum levels at 7-9 weeks after treatment initialization but not in IL 8, VEGF, or LPS add important information on the outcome of advanced HCC patients treated palliatively within the SORAMIC trial.